Mechanisms underlying transient receptor potential ankyrin 1 (TRPA1)-mediated hyperalgesia and edema - Perin-Martins, Andressa; Teixeira, Juliana Maia; Tambeli, Claudia H.; Parada, Carlos Amílcar; Fischer, Luana (Journal of the peripheral nervous system, 2013)
The aim of this study was to investigate the mechanisms that contribute to hyperalgesia and edema induced by TRPA1 activation. The injection of allyl isothiocyanate (AITC, 50, 100, or 300 µg/paw) into the rat's hind paw induced dose and time‐dependent hyperalgesia and edema, which were blocked by the selective TRPA1 antagonist, HC 030031 (1,200 µg/paw), or by treatment with antisense oligodeoxynucleotide (four daily intrathecal injections of 5 nmol). These results demonstrate that the hyperalgesia and edema induced by AITC depend on TRPA1 activation. AITC‐induced hyperalgesia and edema were significantly reduced by treatment with neurokinin 1 (L‐703,606, 38 µg/paw) or calcitonin gene‐related peptide (CGRP8‐37, 5 µg/paw) receptor antagonists, with a mast cell degranulator (compound 48/80, four daily injections of 1, 3, 10, and 10 µg/paw) or with H1 (pyrilamine, 400 µg/paw), 5‐HT1A (wAy‐100,135, 450 µg/paw) or 5‐HT3 (tropisetron, 450 µg/paw) receptor antagonists. Pre‐treatment with a selectin inhibitor (fucoidan, 20 mg/kg) significantly reduced AITC‐induced hyperalgesia, edema, and neutrophil migration. Finally, a cyclooxygenase inhibitor (indomethacin, 100 µg/paw), a β1 (atenolol, 6 µg/paw) or a β2 (ICI 118, 551, 1.5 µg/paw) adrenoceptor antagonist also significantly reduced AITC‐induced hyperalgesia and edema. Together, these results demonstrate that TRPA1 mediates some of the key inflammatory mechanisms, suggesting a key role of this receptor in pain and inflammation.